State of denial - Woodward, Bob 1943- (Simon & Schuster Paperbacks, 2007)
A secret Pentagon assessment sent to the White House in May 2006 forecasted a more violent 2007 in Iraq, contradicting the repeated optimistic statements of President Bush. This book examines how the Bush administration avoided telling the truth about Iraq to the public, to Congress, and often to themselves. In this detailed inside story of a war-torn White House, Woodward answers the core questions: What happened after the invasion of Iraq? Why? How does Bush make decisions and manage a war that he chose to define his presidency? And is there an achievable plan for victory?